Photothermally Crumpled MoS2 Film as an Omnidirectionally Stretchable Platform - Park, Seoungwoong; Song, Jaekwang; Kim, Tae Kyung; Choi, Kwang-Hun; Hyeong, Seok-Ki; Ahn, Minchul; Kim, Hwa Rang; Bae, Sukang; Lee, Seoung-Ki; Hong, Byung Hee (WILEY-V C H VERLAG GMBH, 2022)
Molybdenum disulfide (MoS2) is considered a fascinating material for next-generation semiconducting applications due to its outstanding mechanical stability and direct transition characteristics comparable to silicon. However, its application to stretchable platforms still is a challenging issue in wearable logic devices and sensors with noble form-factors required for future industry. Here, an omnidirectionally stretchable MoS2 platform with laser-induced strained structures is demonstrated. The laser patterning induces the pyrolysis of MoS2 precursors as well as the weak adhesion between Si and SiO2 layers. The photothermal expansion of the Si layer results in the crumpling of SiO2 and MoS2 layers and the field-effect transistors with the crumpled MoS2 are found to be suitable for strain sensor applications. The electrical performance of the crumpled MoS2 depends on the degree of stretching, showing the stable omnidirectional stretchability up to 8% with approximately four times higher saturation current than its initial state. This platform is expected to be applied to future electronic devices, sensors, and so on.